Analytical techniques for serratiopeptidase: A review - Vandana Gupte; Umesh Luthra (Elsevier, 2017)
A review is presented on different analytical techniques used for qualitative and quantitative analysis of serratiopeptidase, a proteolytic enzyme, which has recently gained importance as an anti-inflammatory agent. Efforts have been made to collate all the relevant references to the extent possible. The review discusses the advantages and disadvantages of the cited analytical techniques, which will help to give insights into the methods used for estimation of serratiopeptidase as such, from clinical isolates and from its dosage forms. The review highlights the basic as well as advanced techniques performed for estimating serratiopeptidase. The techniques illustrated here have been demonstrated to be useful for qualitative and quantitative determination of serratiopeptidase and may find application in analyzing other related proteases.